The emergence and epidemic characteristics of the highly mutated SARS‐CoV‐2 Omicron variant. Issue 6 (11th February 2022) - Tian, Dandan; Sun, Yanhong; Xu, Huihong; Ye, Qing
Abstract: Recently, the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) Omicron variant (B.1.1.529) was first identified in Botswana in November 2021. It was first reported to the World Health Organization (WHO) on November 24. On November 26, 2021, according to the advice of scientists who are part of the WHO's Technical Advisory Group on SARS‐CoV‐2 Virus Evolution (TAG‐VE), the WHO defined the strain as a variant of concern (VOC) and named it Omicron. Compared to the other four VOCs (Alpha, Beta, Gamma, and Delta), the Omicron variant was the most highly mutated strain, with 50 mutations accumulated throughout the genome. The Omicron variant contains at least 32 mutations in the spike protein, which was twice as many as the Delta variant. Studies have shown that carrying many mutations can increase infectivity and immune escape of the Omicron variant compared with the early wild‐type strain and the other four VOCs. The Omicron variant is becoming the dominant strain in many countries worldwide and brings new challenges to preventing and controlling coronavirus disease 2019 (COVID‐19). The current review article aims to analyze and summarize information data about the biological characteristics of amino acid mutations, the epidemic characteristics, immune escape, and vaccine reactivity of the Omicron variant, hoping to provide a scientific reference for monitoring, prevention, and vaccine development strategies for the Omicron variant. Highlights: The Omicron variant was the most highly mutated variant of concerns (VOCs). The Omicron variant spread faster than the original virus strain and other VOCs. The Omicron variant produces a higher risk of reinfection than the other variants.